Psychological impact of human-pet interactions in Chinese young people - Yin, Xiaoshan (The University of Edinburgh, 2025)
Despite the growing body of research on human–animal interactions, there remains limited understanding of the psychological impact of pet ownership on young people in China, where pet keeping is notably on the rise, particularly among younger populations. This thesis seeks to enhance our understanding of the psychological effects of pet ownership on young people in China. It comprises six studies: a systematic review focusing on children and young people; three studies based on an online survey of adolescents and emerging adults in China; and two interview studies involving Chinese emerging adult cat and dog owners. Study 1 is a systematic review of research on the health and mental health effects of pet ownership among children and young people in China. A search across eight databases identified 59 studies published between 2002 and 2021, focusing on the health and psychological impacts of pet exposure among individuals from birth to 20 years of age. Pet exposure was most frequently examined as a risk factor for respiratory issues, injuries, and T. gondii infection, but also as a protective factor for cardiovascular health and in mitigating pollution-related respiratory problems. Two studies explored psychological aspects: one investigated post-traumatic stress resulting from animal-induced injuries, and the other examined the benefits of canine-assisted reading activities. These findings underscore the need for further research on the impact of pet ownership on the development and psychological wellbeing of young people in China, which informs the design of Studies 2, 3, and 4. Studies 2, 3, and 4 were based on an online questionnaire survey of Chinese adolescents and emerging adults. Study 2 focused on the motivations for pet ownership in China and employed the Theory of Planned Behaviour as its theoretical framework. A total of 988 adolescents and emerging adults, aged 16 to 29, participated in the study. The results indicated that young people who held more positive attitudes towards pets and perceived stronger subjective norms regarding pet ownership were more motivated to acquire pets. Furthermore, individuals with stronger intentions to keep pets, as well as greater perceived behavioural control, were more likely to actually own pets, providing support for the Theory of Planned Behaviour. Study 3 used the same dataset to examine the relationship between pet ownership and loneliness among Chinese emerging adults, involving 968 participants aged 18 to 29. The findings revealed that emerging adults who owned pets reported lower levels of loneliness and higher life satisfaction. When different types of pet ownership were considered, dog ownership was not associated with either loneliness or life satisfaction, whereas cat ownership was linked to lower levels of loneliness and higher life satisfaction. The pet attachment subscale termed “person substitution” was associated with higher levels of loneliness, while endorsement of animal rights was associated with lower levels of loneliness. Study 4 examined the role of pets in mental health and wellbeing among the same sample as in Study 3. Emerging adults who owned pets reported fewer mental health problems (fewer symptoms of depression, anxiety, and stress) and better overall wellbeing. In addition, both dog and cat ownership were associated with fewer mental health symptoms, although only cat owners reported higher levels of wellbeing. The pet attachment subscale known as “person substitution” was associated with more mental health problems. Building on the reported benefits of pet ownership among emerging adults and the variations identified across different types of pet ownership in the first empirical study, Studies 5 and 6 employed qualitative interviews to further explore the perceived benefits and challenges of cat and dog ownership among emerging adults. Study 5 focused on cat owners. Semi-structured interviews were conducted with 16 emerging adults aged 18 to 29 years from China who currently owned one or more cats but did not own a dog. Thematic analysis was applied to the data, resulting in the identification of four key themes: (1) perception and relationship with cats; (2) perceived benefits of cat ownership; (3) perceived challenges of cat ownership; and (4) mental health and wellbeing. Study 6 focused on dog owners. Semi-structured interviews were conducted with 16 emerging adults aged 18 to 29 years from China who currently owned one or more dogs but did not own a cat. Thematic analysis was applied to the data, resulting in the identification of four key themes: (1) perception and relationship with dogs; (2) perceived benefits of dog ownership; (3) perceived challenges of dog ownership; and (4) mental health and wellbeing. The studies presented in this thesis underscore the significance of pet ownership for the mental health and wellbeing of young people in China. Drawing on a range of research methods, the findings highlight not only the potential benefits of having pets but also the challenges associated with owning different types of animals. These studies address existing gaps in the field of human–animal interaction by focusing on young people in China, a population under-represented in current research yet increasingly engaged in pet ownership. The findings have several practical implications, including the need for educational programmes for pet owners regarding the behaviours and welfare needs of different types of animals, in order to help them manage the challenges of pet ownership. Furthermore, the results inform future research aimed at developing effective pet-related and animal-assisted interventions to improve young people’s experiences of loneliness, life satisfaction, and mental health and wellbeing.
The psychological impact of human-pet interactions in Chinese young people
Keywords: human-animal interactions; young people; children; adolescent; emerging adult; China; pets